Exploring the Role of Place Dependence, Identity, and Positive Experiences in Domestic Tourists’ Revisit Intention - Jellycha Mutiara Kurnia Putri; Putu Gde Arie Yudhistira (Jurnal Manajemen Teori dan Terapan)
Objective: This study investigates the role of place dependence and place identity in shaping domestic tourists' intentions to revisit beach destinations, focusing on the mediating effect of positive emotional experiences.